Enhancing the Middle Management at Individual Level for Organizational Change of an International Airline in Asia - Bhitakburi, Kornchanok (ABAC ODI JOURNAL Vision. Action. Outcome, 2020)
Abstract The purpose of the study is to understand the level of perspectives of change, commitment to service, loyalty to organization, and attitudes towards organizational change of middle managementat Thai Airways International (Public) to enhance and prepare them for organizational change. The respondents have more than 15 years of service in non-overseas assignments with the organization. In an action research design, the study focused on 92 middle managers who were divided into two groups: 46, the experimental group and the other 46, the control group. The experimental group underwent the Team Building, IKIGAI and Appreciative Inquiry (AI) approaches to create self-awareness for organization change. The controlled group did not undergo any activities. Based on the comparative amd analysis, the results showed significant differences on the research variables before and after ODI with the experimental group. Concomitantly, the study confirms that the relationship between perspective of change, commitment to service and loyalty to organization is related and it affects attitudes towards organizational change. The result showed a difference between the two groups on the research variables. Organization Deveopment Iintervention activity is effective as there is difference in the pre and post results on the experimental group. .